2013
DOI: 10.1016/j.repce.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Mesalamine-induced myocarditis following diagnosis of Crohn's disease: A case report

Abstract: Mesalamine is a common treatment for Crohn's disease, and can be rarely associated with myocarditis through a mechanism of drug hypersensitivity. We present the case of a 19-year-old male who developed chest pain two weeks after beginning mesalamine therapy. The electrocardiogram showed slight ST-segment elevation with upward concavity in the inferolateral leads; blood tests demonstrated elevated troponin I and the echocardiogram revealed moderately depressed left ventricular systolic function with global hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Hash shading represents affected area. (A) Patchy, mid-myocardial enhancement in posterior wall and inferior interventricular septum (present case); (B) Subepicardial enhancement in anterior wall and transmural extension in interventricular septum; also in the interatrial septum (not shown);3 (C) Subepicardial enhancement in apical inferior wall and transmural enhancement in interventricular septum;4 (D) Subepicardial enhancement in inferior and lateral walls 2…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Hash shading represents affected area. (A) Patchy, mid-myocardial enhancement in posterior wall and inferior interventricular septum (present case); (B) Subepicardial enhancement in anterior wall and transmural extension in interventricular septum; also in the interatrial septum (not shown);3 (C) Subepicardial enhancement in apical inferior wall and transmural enhancement in interventricular septum;4 (D) Subepicardial enhancement in inferior and lateral walls 2…”
Section: Discussionmentioning
confidence: 76%
“…The exact mechanism for mesalamine-induced myocarditis is not well established;4 however, patients typically present with symptoms within 2–4 weeks after initiation (sometimes delayed when corticosteroids are used concurrently) 2. Common signs and symptoms of mesalamine-induced myocarditis include substernal chest pain, dyspnoea, fever, leucocytosis, elevated cardiac enzymes and inflammatory markers, T-wave or ST-segment abnormalities (T-wave flattening is particularly common) and LVSD 1.…”
Section: Discussionmentioning
confidence: 99%